CLUSTERING NACL SOLUTION CONCENTRATION BASED ON IMPEDANCE, CONDUCTIVITY, AND TDS PARAMETERS USING A PCA APPROACH WITH K-MEANS CLUSTERING - Wismaya, Herenda Sela; Sugianto, Wahyu (Universitas PGRI Sumatera Barat, 2023)
A research study requires an approach to implement research data more optimally and be easily interpretable. The PCA approach with K-means clustering is an appropriate method for clustering NaCl solution concentrations based on impedance, TDS, and conductivity parameters. The results of this method indicate that the first and second principal components with eigenvalues of 2.7208 and 1.2728, respectively, represent 68.0% and 31.8% of the total variability. Cumulatively, these two principal components account for 99.8% of the total variance. This suggests that the approach used aligns well with the tested parameters. Therefore, it can be concluded that the PCA approach with K-means clustering can be used to cluster NaCl solution concentrations, distinguishing between low and high concentrations of NaCl solutions